Epileptic myoclonus - M. B. Mironov; S. G. Burd; Yu. V. Rubleva; T. M. Krasilshchikova; R. T. Tairova (Эпилепсия и пароксизмальные состояния)
The article presents the main definitions, classification, and electroclinical characteristics of epileptic myoclonus.